30 Whole body contrast enhanced MRA can quantify and monitor atherosclerosis progression. (26th April 2015) - Weir-McCall, JR; White, RD; Gandy, SJ; Ramkumar, PG; Belch, JJF; Struthers, AD; Houston, JG
Abstract : Aim: To determine the ability of whole body magnetic resonance angiography (WB-MRA) to measure global atheroma burden progression. Methods: 50 consecutive patients with symptomatic peripheral arterial disease referred for clinical MRA were recruited. WB-MRA was performed at baseline, 6 months and 3 years. WB-MRA data was analysed by dividing the vasculature into 31 anatomical arterial segments. Each segment was scored according to degree of luminal narrowing: 0=normal, 1 = <50%, 2 = 50–70%, 3 = 71–99%, 4 = vessel occlusion. From this a standardised atheroma score (SAS) was calculated with a maximum score of 100 and minimum score of 0. Progression was assessed with repeat measure ANOVA. Results: 36 patients were scanned at 0 and 6 months, with 26 patients scanned at the three year follow up. Only those who completed all 3 visits were included in the final analysis. At 3 years, n = 18 demonstrated atheroma progression while n = 8 showed stable or improved disease. Those with no progression had significantly lower baseline SAS, and were more likely to be on statin therapy (p < 0.05 for both). Baseline SAS was 15.7 ± 10.3 at baseline with no progression at 6 months (SAS=16.4 ± 10.5, p = 0.67). At 3 years there was significant progression in atheroma (SAS = 17.7 ± 11.5, p = 0.01) (Figure 1 ). On multiple linear regression, age (β 0.14 p = 0.014), pulse pressure (β −0.12 p = 0.005) and ankle-brachial pressure index (β −7.7 p = 0.036) were independently associated with the rate of progression. Conclusion: Whole body contrast enhanced MRA can quantify and monitor atherosclerosis progression at 3 year follow-up even in a small cohort.